Profitability of the cultivation of tara Caesalpinia spinosa (Molina) Kuntze in Apurímac, Perú - Gómez Oscorima, Raquel (2023)
Given its potential to improve the peasant economy, for its growing exports due to the multiple uses of its derivatives, the objective is to analyze the improvement in profitability of the cultivation of Caesalpinia spinosa (Molina) Kuntze tara in Apurímac instead of simply collecting it. To test the hypothesis that growing tara is more profitable than harvesting it, the partial budget is used to obtain benefits per hectare in the short term, and the cash flow to assess the magnitude of the long-term increase in profitability. As agriculture is subject to risks, a probabilistic approach is employed with the help of software @Risk. It is concluded that the tara has higher profitability than the collected product, which would explain the progress of the sowing of this crop in Apurimac and Peru so it is recommended to the institutions interested in the development of the Peruvian Andes, also evaluate the economic benefits of growing other forest species.